Adaptive inner iteration processes in pressure-based method for viscous compressible flows. (2nd September 2018) - Wang, Jin-Ping; Zhang, Jian-Fei; Qu, Zhi-Guo; Tao, Wen-Quan
Abstract: In some pressure-based methods, inner iteration processes are introduced to achieve efficient solutions. However, number of the inner iteration is fixed as 2 or 4 for different computations. In this paper, a mechanism is proposed to control inner iteration processes to make the number of inner iterations vary adaptively with different problems. The adaptive inner iteration processes are used in viscous compressible flows. Results reveal that by introducing inner iteration processes, computational efficiency is highly improved compared with that of the solution without inner iteration. In addition, adaptive inner iteration solutions have better robustness than fixed inner iteration solutions.